Potensi Sari Buah Belimbing Wuluh (Averrhoa bilimbi. L) Sebagai Terapi Adjuvan Retinopati Diabetes - I Made Merta Jaya (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
Diabetes mellitus is a disorder of glucose metabolism in the body caused by abnormalities in secretion and/or insulin secretion. The prevalence of diabetes mellitus based on the World Health Organization in 2014 is around 422 million adults or around 8.5% of the world's population. The prevalence in Indonesia in 2016 is 6.9% of Indonesia's population. Diabetes Mellitus patients who are not managed properly will cause various kinds of complications. One of the highest complications is Diabetic Retinopathy. Diabetic retinopathy if not treated promptly can cause blindness. In recent years people prefer traditional medication for their medicine because it has fewer side effects. Belimbing Wuluh (Averrhoa Bilimbi. L) is a plant that has many health benefits. One of the benefits is to have antidiabetic effects and as adjuvant therapy for diabetic retinopathy. Belimbing wealth (Averrhoa Bilimbi. L) contains several active compounds, there are flavonoids, saponins, and vitamin C. All three of these active ingredients work by inhibiting the pathway of polyols, inflammation, and free radicals.